Life on the stoichiometric knife-edge: effects of high and low food C:P ratio on growth, feeding, and respiration in three Daphnia species. Issue 2 (1st January 2016) - Elser, James J.; Kyle, Marcia; Learned, Jennifer; McCrackin, Michelle L.; Peace, Angela; Steger, Laura
Abstract: Recently, data have emerged indicating that not only high food carbon:phosphorus (C:P) ratio but also low food C:P (P-rich food) can have negative effects on the growth of consumers. The shape of this "stoichiometric knife edge, " however, is not yet well-documented, and the mechanisms underpinning it are not understood. Here we report the results of experiments using 3 species of Daphnia ( D. magna, D. pulicaria, D. pulex ) consuming the green alga Scenedesmus acutus with widely varying C:P ratios (from <50 to >1500 by atoms). The experiments were designed to (1) characterize the potential stoichiometric knife edge for each species, and (2) evaluate potential changes in feeding and respiration rates that may underpin the unimodal response to food C:P. All 3 Daphnia species grew more slowly when food C:P (atomic) exceeded ~250–300 but also when C:P was <120. Both high and low C:P foods were associated with increased respiration rates, indicating that the negative effects of food C:P imbalance at least partially involve increased metabolic costs of dealing with stoichiometrically imbalanced food. Feeding rate experiments indicated that, in contrast with limited previous data, animals generally increased their feeding rate on P-rich food. Overall, the "lower threshold elemental ratio" we identify here (~120) is surprisingly high, in an ecologically meaningful range, suggesting that negative effects of excessive food P content may play an under-recognized role in affecting Daphnia performance in P-rich lakes with low seston C:P ratio. Such effects also need to be incorporated into stoichiometrically explicit models of planktonic trophic interactions.